Sustainable Digital Transformation in Logistics: A Regression Modeling Approach to Logistics 4.0 Awareness - Irmak, Esma; Pelit, Irem (International Review of Management and Marketing, 2026)
The ever increasing digital transformation in the logistics sector contributes to sustainable development goals. This study investigated the awareness levels of Logistics 4.0 among companies operating in national and international markets, members of the International Association of Transport and Logistics Service Providers (UTIKAD). Data were collected using a survey developed in 2020 (Çiçekli, 2020). The survey was distributed to the firms via email, and statistical analyses were performed using the responses received from 110 companies. All statistical procedures were carried out using the SPSS 25.0 software package. After confirming that the dataset was suitable for factor analysis, a Principal Component Analysis (PCA) was conducted. Four factors were identified: economic benefit, firm structure, digital technology usage, and awareness. To determine the variables that influence firms’ awareness of Logistics 4.0, a multiple linear regression analysis was performed. The results revealed that the most significant predictors of Logistics 4.0 awareness were the economic benefit and digital technology usage variables.